Tailoring the secretome composition of mesenchymal stem cells to augment specific functions of epidermal regeneration: an in vitro diabetic model - Hodge, Jacob G.; Robinson, Jennifer L.; Mellott, Adam J. (Frontiers in Medical Technology, 2023)
Introduction Wound healing consists of a dynamic series of events that are highly dependent on paracrine factors for proper progression through the phases of wound healing. Inappropriate progression through the phases is associated with insufficient epidermal regeneration (i.e., re-epithelialization) of wounds and subsequent propagation of chronic wounds, such as diabetic ulcers, which are associated with increased patient morbidity. Recently, investigation into the dynamic secretome of Adipose-derived Mesenchymal Stem Cells (ASCs), have shown promise in augmenting the wound healing response of chronic diabetic wounds. However, currently utilized 2D culture techniques are known to drastically alter the regenerative phenotype of ASCs. In this study a novel tissue-mimetic 3D system was utilized as a means to culture ASCs. Methods The capacity for the ASC secretome to augment epidermal regeneration activity was then evaluated after exposure of ASCs to “wound priming stimuli” in 2D and 3D. The priming stimuli consisted of coating the 2D and 3D systems with the wound matrix proteins, collagen type I, fibronectin, and fibrin. To understand the potential benefit of the ASC secretome in the context of diabetic wounds, keratinocytes (KCs) were exposed to super-physiological glucose levels to induce a diabetic-like phenotype (idKCs). Results Relative to KCs, idKC exhibited a 52% and 23% decline in proliferation and migration, respectively. Subsequently, analyses of the ASC secretome were performed. ASC conditioned media (ASC-CM) from tissue-mimetic culture demonstrated a > 50% increase secretion of proteins and a 2-fold increase in secreted EVs, relative to 2D culture. Interestingly, the different priming stimuli did not alter the total amount of protein or EVs secreted within the tissue-mimetic system. However, evaluation of specific soluble proteins via ELISA revealed significant differences in key epidermal regeneration factors, such as EGF, IGF-1, FGF-2, MMP-1, TIMP-1, and TGFβ-1. Additionally, the relative effect of ASC-EVs from the 2D and 3D system on idKCs epidermal regeneration functionality varied significantly, with EVs from 3D-Collagen culture providing the most significant benefit on idKC activity. Discussion Together, these data support the utilization of tissue-mimetic culture system to enhance the adaptability and secretory activity of MSC-like populations in order to generate tailored biologics, via priming stimuli, for specific wound healing applications.